IMPLEMENTASI AKAD IJARAH MUNTAHIYAH BITTAMLIK PADA PRODUK PEMBIAYAAN PT. BANK MUAMALAT INDONESIA, Tbk KANTOR CABANG BINJAI - Devy Asmita; Khairani Sakdiah; Anjur Perkasa Alam (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study focuses on the discussion of the form of the contract used, the clauses offered, the procedure for implementing the financing, the financing process as well as the public's interest in financing the Ijarah Muntahiyah Bittamlik contract at PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office. The research method used in this study is a descriptive qualitative research method with an empirical approach. Informants in this study were employees of PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office deemed able to provide information related to the implementation of the Ijarah Muntahiyah Bittamlik contract. In this study, researchers used a collection technique, namely by means of observation, interviews, and documentation. Data analysis in this study consisted of data reduction, triangulation and conclusion drawing. The results of the study explain that the form of the Ijarah Muntahiyah Bittamlik contract is an underhand deed, meaning that the agreement is made only between the bank and the customer without asking for help from the authorized official, in this case a notary. In the Ijarah Muntahiyah Bittamlik contract financing agreement at PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office has several choices of contract forms that can be used, including standard agreements, named contracts, principal contracts, accessory contracts and maturity contracts. The implementation of the Ijarah Muntahiyah Bittamlik transaction is based on the transfer of benefits (use rights), not ownership transfers (property rights). So basically the principle of Ijarah Muntahiyah Bittamlik is the same as the principle of buying and selling, but the difference lies in the object of the transaction. When in buying and selling the object of transaction is goods, while in ijarah the object of transaction is goods or services. Ijarah Muntahiyah Bittamlik financing product at PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office is in great demand by the Muslim community today because this contract is very profitable for the customer because the goods being leased will become the property of the lessee.